Brunstvisningsförmåga hos mjölkkor - en beteendenstudie - Smedberg, Klara (2012)
Oestrus in dairy cattle has changed over the last decades; the intensity of oestrus has declined and the duration decreased. Several studies have shown that not all dairy cows stand to be mounted, and that oestrus expression in many cases may be characterized by other behaviours. The aim of this study was to investigate oestrus behaviour in a herd of todays’ high producing dairy cattle. The study was carried out at Jälla naturbruksgymnasium in Uppsala during one week in January 2011. Twenty-eight cows (28 Swedish red breed and 10 Holstein) were included in the study, and 9 (7 Swedish red breed and 2 Holstein) of these ovulated during the study. For comparison of behaviour during oestrus with behaviour during other periods of the oestrus cycle, 9 control cows were chosen from the remaining 19 cows included in the study. The cows were observed for 4 periods á 2 hours each day during one week. The number of times a cow performed or received a sexual or social behaviour, or showed restlessness, was recorded. A comparison was made between the results from the behavioural study and the registrations from the regular oestrus detection routine in the herd, and a difference in oestrus expression was seen for several cows. Standing oestrus was observed in 44 % (4/9) of the cows. Mounts/attempts to mount were the most common sexual behaviour, followed by chin-resting. Activity increased drastically during oestrus compared to other periods of the oestrus cycle, for sexual behaviours as well as for social behaviours and restlessness. The proportion of mounts/attempts to mount was three times greater during oestrus compared to during non-oestrus. However, the proportion of head butts was smaller during oestrus compared to non-oestrus. Oestrus expression was strongest when more than one cow was in oestrus at the same time. Sexual activity was highest during nighttime. The study also supports findings in previous research reports that the oestrus period has shortened during recent decades; only one of the four cows that stood to be mounted during the study did so during more than one observation period of 2 hours. No oestrus expression was shown by cows that had their first ovulation after calving. Oestrus expression was also weak at the second ovulation. A distinct oestrus expression was shown from ovulation number three. In conclusion, the results from this study are in line with what has been reported in studies from other countries in recent years – that the character of oestrus in dairy cattle has changed, and that the duration of oestrus has decreased.